Increased frequency of CCR7+CD4+ T cells from patients with primary Sjögren's syndrome: An indicator of disease activity rather than of damage severity. (October 2018) - Wu, Chunling; Yang, Pingting; Liu, Haina; Xiao, Weiguo; Zhao, Lijuan
Abstract: Expression of CCR7 on T cells has been reported to be associated with the lymphocytic migration and infiltration, which is recognized as a vital part of the pathogenesis of Primary Sjögren's syndrome (pSS). Here, we compared the expression of CCR7 on CD4+T cells between pSS patients and control groups, including healthy donors (HD) and patients with systemic lupus erythematosus (SLE) and examined correlations with disease activity and damage severity, which were evaluated by EULAR Sjögren's Syndrome Disease Activity Index (ESSDAI) and Sjogren's Syndrome Disease Damage Index (SSDDI), respectively. Peripheral blood mononuclear Cells (PBMC) were obtained from patients and controls and expressions of CCR7 were evaluated by flow cytometry. CCR7 was selectively and frequently expressed on CD4 + T cells, but less on CD8 + T cells of patients with pSS. In contrast, this phenomenon was neither seen in normal subjects nor in patients with SLE. The expression level of CCR7 in the peripheral blood CD4 + T cells is closely correlated with ESSDAI, but not SSDDI. Correspondently, the chemotactic index (CI) of CD4 + T cells was higher than CD8 + T cells in patients with pSS. Furthermore, the CI of CD4 + T cells is also higher than that of other controls, which is correlated with ESSDAI. All the findings suggested that CCR7 might play an important role in the development of pSS by mediating the migration of CD4 + cells. Thus, the expression of CCR7 in CD4 + T cells is probably a useful biomarker to evaluate and monitor disease activity. CCR7 can also potentially be a novel target for the therapy of pSS.